Ornament sznurowy na ceramice ludności Kultury Amfor Kulistych z Poznania-Nowego Miasta (stan. 314) - Michałowski, Andrzej; Sikorski, Andrzej (Wydawnictwo Naukowe UAM, 2005)
The article discusses a corded decoration on pottery from the Amphorae Globular Culture seasonal camp. Analysis of impressions on the pot outer surfaces revealed that this characteristic motif was produced by a simple textile template. Fragments of a five-stranded cord (S/3S/2Z) - certainly not a two-stranded one - were sewn on a net 'band' (item of a sprang type). This technique guaranteed a precise layout and space between particular impressions (ca. 2 mm each) on a soft amphorae (?) surface irrespective of an angle of ornament placements and decorative element joints.
A corded ornament on the globular Amphorae Culture Pottery from Poznań-Nowe Miasto (site 314)